Hidden amorphous phase and reentrant supercooled liquid in Pd-Ni-P metallic glasses - S. Lan (Nature Portfolio, 2017)
An anomalous exothermal calorimetric peak far below crystallization temperatures in prototypical Pd-Ni-P glasses has been recognized for four decades. Here authors use neutron and high-energy X-ray diffraction to find evidence for a polyamorphous phase transition where medium-range order undergoes large changes while short-range order changes little.